2022
DOI: 10.1002/syn.22247
|View full text |Cite
|
Sign up to set email alerts
|

Association between abnormal brain oscillations and cognitive performance in patients with bipolar disorder: Molecular mechanisms and clinical evidence

Abstract: Brain oscillations have gained great attention in neuroscience during recent decades as functional building blocks of cognitive-sensory processes. Research has shown that oscillations in "alpha," "beta," "gamma," "delta," and "theta" frequency windows are highly modified in brain pathology, including in patients with cognitive impairment like bipolar disorder (BD). The study of changes in brain oscillations can provide fundamental knowledge for exploring neurophysiological biomarkers in cognitive impairment.Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 179 publications
(251 reference statements)
0
9
0
Order By: Relevance
“…Alterations in processes that regulate synaptic plasticity and PSD architecture may affect brain connectivity, disrupting the synchronized firing of those neurons organized in a high-frequency oscillation network (30–90 Hz/s), known as gamma waves, involved in cognition and memory functions [ 33 , 34 , 35 ]. Studies have associated altered gamma oscillations with neurological and psychiatric disorders, including Alzheimer’s disease, Parkinson’s disease, and schizophrenia [ 36 , 37 ]. Moreover, gamma oscillations were demonstrated to be modulated by antipsychotic treatment in preclinical studies [ 38 , 39 , 40 ].…”
Section: The Close Relationship Between Brain Functional Connectivity...mentioning
confidence: 99%
“…Alterations in processes that regulate synaptic plasticity and PSD architecture may affect brain connectivity, disrupting the synchronized firing of those neurons organized in a high-frequency oscillation network (30–90 Hz/s), known as gamma waves, involved in cognition and memory functions [ 33 , 34 , 35 ]. Studies have associated altered gamma oscillations with neurological and psychiatric disorders, including Alzheimer’s disease, Parkinson’s disease, and schizophrenia [ 36 , 37 ]. Moreover, gamma oscillations were demonstrated to be modulated by antipsychotic treatment in preclinical studies [ 38 , 39 , 40 ].…”
Section: The Close Relationship Between Brain Functional Connectivity...mentioning
confidence: 99%
“…2 E-J), Spearman’s correlation coefficient between node strength and each receptor’s or transporter’s density across parcels. We first assessed the GABA A and NMDA receptors, which through fast ionotropic transmission shape the generation of oscillations in local circuits of interacting glutamatergic excitatory pyramidal cells (PCs) and inhibitory GABAergic interneurons (INs) (Batista-Brito et al, 2018; Liley & Muthukumaraswamy, 2020; Lozano-Soldevilla et al, 2014; Lu et al, 2022; Middleton et al, 2008; Roopun, 2008). We found that both GABAa and NMDA receptor densities covaried positively with the PS node centrality in δ to α and γ bands, but with AC node centrality only in γ band (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We specifically established how the heterogeneity in receptor and transmitter densities influences networks of phase synchrony and amplitude correlations. One limitation of the current study is the lack of usable density maps for some important receptors such as GABA B that are known to be important for the generation of cortical oscillations in microcircuits (Liley & Muthukumaraswamy, 2020; Lozano-Soldevilla et al, 2014; Lu et al, 2022). Future studies will need to investigate how these microcircuits are influenced by the underlying neurotransmitter receptor and transmitter densities not only in resting state, but also during task (Boot et al, 2017; Cools, 2008; Puig & Gulledge, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Insufficient GABAergic neurotransmission and excessive glutamatergic system activity have previously been linked to electrophysiological alterations in BD [92]. Considering that mood stabilisers for BD, such as valproate and lithium, may have opposing effects on beta activity and potentially on beta/gamma connectivity [92,93], a promising avenue for future research is to assess the modulation of alpha-beta and gamma amplitude and connectivity during pwPE encoding in BD as potential markers for tracking treatment response and for diagnostic purposes. A key limitation of our study is the inclusion of patients on diverse psychiatric medications, including mood stabilisers, antipsychotics, and antidepressants.…”
Section: Discussionmentioning
confidence: 99%